2020
DOI: 10.1101/2020.08.17.254250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causal evidence for the adaptive benefits of social foraging in the wild

Abstract: Sociality is a fundamental organizing principle across taxa, thought to come with a suite of adaptive benefits. However, making causal inferences about these adaptive benefits requires experimental manipulation of the social environment, which is rarely feasible in the field. Here we manipulated the number of conspecifics in Trinidadian guppies (Poecilia reticulata) in the wild, and quantified how this affected a key benefit of sociality, social foraging, by investigating several components of foraging success… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…The present study is relevant to empirical research on the sociality of animal populations (Dall et al 2004; Sih et al 2004; Dingemanse and Réale 2005; Evans et al 2020). In particular, a number of studies have shown that variation in sociality influences the spread of social information (Aplin et al 2012; Allen et al 2013; Farine et al 2015a; Snijders et al 2021). For example, the social network attributes of wild great tits ( Parus major ) can be used to predict the discovery rate of novel food patches (Aplin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is relevant to empirical research on the sociality of animal populations (Dall et al 2004; Sih et al 2004; Dingemanse and Réale 2005; Evans et al 2020). In particular, a number of studies have shown that variation in sociality influences the spread of social information (Aplin et al 2012; Allen et al 2013; Farine et al 2015a; Snijders et al 2021). For example, the social network attributes of wild great tits ( Parus major ) can be used to predict the discovery rate of novel food patches (Aplin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prominent examples of a dynamic benefit of sociality is social information, which can provide individuals with knowledge about ephemeral resources or conditions, such as foraging or nesting sites, or predation risk (Doligez et al 2002; Danchin et al 2004; Valone 2007). This information can be transmitted through active signalling (Elgar 1986) or via inadvertent cues (Pöysä 1992; Galef and Giraldeau 2001), with highly social individuals likely to receive information sooner than poorly connected members of the population (Aplin et al 2012, 2015a; Snijders et al 2021). We should therefore expect sociality to increase access to survival-related information, but as is the case with disease, the prevalence of information in the population will depend on sociality, forming an eco-evolutionary feedback that causes the evolution of sociality to diverge from the fixed-benefit scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Model selection was conducted with R version 4.0.2 76 in R Studio version 1.2.5033 (©2009-2019 RStudio, Inc.). All the data and code generated and analyzed during this study are available in the Open Science Framework repository 77 . Models I and III (binary dependent variable) were analyzed with generalized linear mixed models (GLMM) with a binomial error distribution and logit link function using the glmer function from the 'lme4' package 78 , fitted by maximum likelihood (Laplace approximation) using the bobyqa optimizer.…”
Section: Methodsmentioning
confidence: 99%
“…All the data generated and analyzed during this study are available in the Open Science Framework repository, https://osf.io/csajg 77 .…”
Section: Data Availabilitymentioning
confidence: 99%
“…Individuals benefit from foraging socially through diverse mechanisms such as local enhancement (e.g., cues from successful foragers provide information about food location) or social facilitation (e.g., initiating foraging quicker in the presence of foraging conspecifics), which allow an increase in food detection and foraging success (Galef & Giraldeau, 2001; Giraldeau & Beauchamp, 1999; Giraldeau & Caraco, 2018; Grand & Dill, 1999; Pitcher et al, 1982; Snijders et al, 2021; Ward & Zahavi, 1973). Such benefits are thought to be due to an increased sensorial scope, which allows for more information to be collected and disseminated within the group (Clark & Mangel, 1986).…”
Section: Introductionmentioning
confidence: 99%